The Enemy Within : A History of Espionage - Crowdy, Terry (UK Osprey Publishing, 2006)
"To gain the upper hand in conflict the ability to know what your enemy is planning is vital. Massive amounts of money have been spent and many lives have been lost in pursuit of this objective. From biblical times to the present day, leaders have employed espionage on and off the battlefield in the quest for victory. Tactics might differ, from dirty tricks and theft to interrogation and torture
Include End Notes, Bibliography, Index and Illustrations
Keywords: Espionage -- History. -- Military Intelligence -- History. -- Espionage